2021
DOI: 10.1101/2021.04.13.21255139
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strong anti-viral responses in pediatric COVID-19 patients in South Brazil

Abstract: Epidemiological evidence that COVID-19 manifests as a milder disease in children compared to adults has been reported by numerous studies, but the mechanisms underlying this phenomenon have not been characterized. It is still unclear how frequently children get infected, and/or generate immune responses to SARS-CoV-2. We have performed immune profiling of pediatric and adult COVID-19 patients in Brazil, producing over 38 thousand data points, asking if cellular or humoral immune responses could help explain mi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…16,35,49,50 Results of T cell responses against N and membrane proteins are conflicting with some studies showing lower levels in children 50 and others higher levels. 16,35,49 Adults infected with SARS-CoV-2 typically have a decreased lymphocyte count, with reduced numbers of naïve CD4+ and CD8+, T regulatory and memory T cells. [51][52][53] One study reported that acute and memory SARS-CoV-2-specific CD4+ cells increase with age.…”
Section: Systemic Adaptive Immunitymentioning
confidence: 99%
See 4 more Smart Citations
“…16,35,49,50 Results of T cell responses against N and membrane proteins are conflicting with some studies showing lower levels in children 50 and others higher levels. 16,35,49 Adults infected with SARS-CoV-2 typically have a decreased lymphocyte count, with reduced numbers of naïve CD4+ and CD8+, T regulatory and memory T cells. [51][52][53] One study reported that acute and memory SARS-CoV-2-specific CD4+ cells increase with age.…”
Section: Systemic Adaptive Immunitymentioning
confidence: 99%
“…50 Furthermore, they have lower T cell responses to S and ORF1 proteins and reduced CD4+ T cell effector memory. 16,35,49,50 Results of T cell responses against N and membrane proteins are conflicting with some studies showing lower levels in children 50 and others higher levels. 16,35,49…”
Section: Mechanisms Which Are More Likely To Contribute To the Age-re...mentioning
confidence: 99%
See 3 more Smart Citations